INCREASED EXPRESSION OF EPITHELIAL SODIUM CHANNEL AFFECTS MECHANICAL PROPERTIES OF ENDOTHELIAL CELLS BY REORGANISING THE F-ACTIN CYTOSKELETON. (April 2021) - Shah, Vikash Kumar; Fronius, Martin
Abstract : Objective: Epithelial sodium channel (ENaC) in the kidney maintain body salt/water balance and regulate blood pressure. Recent finding suggests that endothelial cells express ENaC. Here elevated ENaC contributes to increased endothelial cell stiffness (ECS) that associates with endothelial dysfunction and hypertension. dysfunction and hypertension. However, the mechanism how ENaC influence ECS remains unknown. This study aims to investigate the potential role of ENaC subunits in mediating ECS by cytoskeletal changes. I hypothesize ENaC mediated ECS via an increased expression of F-actin. To challenge our hypothesis, ENaC protein expression was quantified by Western blot in human umbilical vein endothelial cells (HUVECs) treated with aldosterone under static condition (0 dyn/cm 2 ) and under laminar shear stress (LSS, 10 dyn/cm 2, 24 h). Atomic Force Microscopy (AFM) was used to measure cell stiffness and changes of F-actin were assessed by immunofluorescence microscopy. Under static condition, aldosterone significantly increased ?-, and ?-ENaC protein levels. On the other hand, under LSS conditions aldosterone increased ?-, and ?-ENaC protein levels. Also under static condition, a significantly increased Young's modulus was determined in both fixed and live HUVEC cells treated with aldosterone. Furthermore, the increased stiffness in aldosterone treated cells revealed increased F-actin levels. Overall, these findings indicate that aldosterone has different effects on ENaC subunit expression in HUVECs grown under static and LSS conditions. The increased ENaC expression does increase ECS. This seems to involve an increased F-actin expression as a major determinant of ECS. Therefore, this study may provide a new mechanism for ENaC-mediated ECS and blood pressure regulation.